2017
DOI: 10.11648/j.ajac.20170501.12
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analytical Evaluation of the Trivedi Effect<sup>®</sup> - Energy of Consciousness Healing Treatment on the Physical, Structural, and Thermal Properties of Zinc Chloride

Abstract: Abstract:Zinc chloride has an importance in pharmaceutical and nutraceutical industries for the prevention and treatment of several diseases. The objective of the current study was to investigate the impact of The Trivedi Effect ® -Energy of Consciousness Healing Treatment (Biofield Energy Treatment) on physical, structural, and thermal properties of zinc chloride using PXRD, PSD, FT-IR, UV-vis, TGA, and DSC analysis. Zinc chloride was divided into two parts -one part was control, while other part was treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…The data was collected in the form of a chart of the Bragg angle (2θ) vs. intensity (counts per second), and a detailed table containing information on peak intensity counts, d value (Å), relative intensity (%), full width half maximum (FWHM) (°2θ), area (cts*°2θ) using X'Pert data collector and X'Pert high score plus processing software. The crystallite size (G) was calculated from the Scherrer equation following the literature [11,12,[35][36][37]. The crystallite size (G) was calculated by using the following equation 1:…”
Section: Powder X-ray Diffraction (Pxrd) Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The data was collected in the form of a chart of the Bragg angle (2θ) vs. intensity (counts per second), and a detailed table containing information on peak intensity counts, d value (Å), relative intensity (%), full width half maximum (FWHM) (°2θ), area (cts*°2θ) using X'Pert data collector and X'Pert high score plus processing software. The crystallite size (G) was calculated from the Scherrer equation following the literature [11,12,[35][36][37]. The crystallite size (G) was calculated by using the following equation 1:…”
Section: Powder X-ray Diffraction (Pxrd) Analysismentioning
confidence: 99%
“…The particle size analysis of ferrous sulphate was conducted on Malvern Mastersizer 3000, UK with a detection range between 0.01 µm to 3000 µm using wet method [11,12,35,36]. The sample unit (Hydro MV) was filled with a dispersant medium (Light liquid paraffin oil) and operated the stirrer at 2500 rpm.…”
Section: Particle Size Analysis (Psa)mentioning
confidence: 99%
See 2 more Smart Citations
“…The Trivedi Effect ® -Energy of Consciousness Healing Treatment significantly altered physicochemical properties such as crystalline structure, crystallite size, particle size, surface area, and thermal stability through introducing a polymorph of the pharmaceutical/nutraceutical compound. It was suggested that Biofield Energy Treated pharmaceutical/nutraceutical compounds could have more bioavailable and thermally stable compared with the untreated compounds [22][23][24][25][26]. The physicochemical and thermal properties etc.…”
Section: Introductionmentioning
confidence: 99%